Spaced Noninvasive Brain Stimulation: Prospects for Inducing Long-Lasting Human Cortical Plasticity. (September 2015) - Goldsworthy, Mitchell R.; Pitcher, Julia B.; Ridding, Michael C.
Neuroplasticity is critical for learning, memory, and recovery of lost function following neurological damage. Noninvasive brain stimulation (NIBS) techniques can induce neuroplastic changes in the human cortex that are behaviorally relevant, raising the exciting possibility that these techniques might be therapeutically beneficial for neurorehabilitation following brain injury. However, the short duration and instability of induced effects currently limits their usefulness. To date, trials investigating the therapeutic value of neuroplasticity-inducing NIBS have used either single or multiple treatment sessions, typically repeated once-daily for 1 to 2 weeks. Although multiple stimulation sessions are presumed to have cumulative effects on neuroplasticity induction, there is little direct scientific evidence to support this "once-daily" approach. In animal models, the repeated application of stimulation protocols spaced using relatively short intervals (typically of the order of minutes) induces long-lasting and stable changes in synaptic efficacy. Likewise, learning through spaced repetition facilitates the establishment of long-term memory. In both cases, the spacing interval is critical in determining the outcome. Emerging evidence in healthy human populations suggests that the within-session spacing of NIBS protocols may be an effective approach for significantly prolonging the duration of induced neuroplastic changes. Similar to findings in the animal and learning literature, the interval at which spaced NIBS is applied seems to be a critical factor influencing the neuroplastic response. In this Point of View article, we propose that to truly exploit the therapeutic opportunities provided by NIBS, future clinical trials should consider the optimal spacing interval for repeated applications.